Numerical modeling of links behavior in eccentric bracings with dual vertical links - Saeid Sabouri-Ghomi; Behnam Saadati (Numerical Methods in Civil Engineering)
Configuration and geometry of bracing systems affect the seismic performance of structures significantly. Recently, the current authors have introduced a new configuration for eccentric bracing of structural frames that may be assumed as the combination of inverted Y-type and rotated K-type EBFs. The resulted braced frame is called EBF-DVL, consisting of two vertical links attached together by a horizontal link. For evaluating the vertical links of EBF-DVL in seismic conditions, a total number of 4 cyclic quasi-static tests were performed on the specimens with different link lengths, sections and material grades. In this research, a summary of tests performed on experimental specimens are presented at first. Afterwards, the results of numerical modeling using ABAQUS software are described and compared with the experimental results. Cyclic loading was applied on each model, similar to the deformation history which was used during the tests. The effects of both material and geometry nonlinearities are considered. The diagrams of Load-displacement resulted from numerical analyses have a good agreement with the experimental ones although there is more inconsistency in cases with steeper softening behavior. Also, the behavior of the links' components and yielding sequences are the same as experimental specimens.